5(3.4+-0.6y)+6y=-8

Simple and best practice solution for 5(3.4+-0.6y)+6y=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3.4+-0.6y)+6y=-8 equation:


Simplifying
5(3.4 + -0.6y) + 6y = -8
(3.4 * 5 + -0.6y * 5) + 6y = -8
(17 + -3y) + 6y = -8

Combine like terms: -3y + 6y = 3y
17 + 3y = -8

Solving
17 + 3y = -8

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 3y = -8 + -17

Combine like terms: 17 + -17 = 0
0 + 3y = -8 + -17
3y = -8 + -17

Combine like terms: -8 + -17 = -25
3y = -25

Divide each side by '3'.
y = -8.333333333

Simplifying
y = -8.333333333

See similar equations:

| 5x^4-38x^2-16=0 | | g^2-11g+30=0 | | 17.25=x+(x*.15) | | 10x-4=0 | | 52=4x-16 | | -9(-1)+4(-3.1)= | | 3(-1)-7(-3.1)= | | 6xy=10+-4y | | -x/3=-2 | | 9(t-5)+6t=5(3t+3)-10 | | 27X-90+40X+60+20=3X+18+16+68X | | -9x+4(-3.1)=-3 | | 5f/3=-7 | | 4+4s-2=9s+4-3s | | -9(6+2.3y)+4y=-3 | | 7.5x=2000 | | 2(3x-1)-(4x-3)+x=5(x+2)-3(x-2)-15 | | 3(6)-7(0)= | | 5x-1+2=10 | | (5/8)^-1 | | 3x-7(0)=18 | | 3(6+2.3y)-7y=18 | | 37X-90+40=12X+25X+50 | | 8-v^3=0 | | 3x+15=53 | | 282-3x=42x-22 | | 8t^2-4t^3=-60t | | x+y=160 | | -4+6(x-5)=12x+6-6x | | 0=1+2+3(21+30+4M) | | N-7=21 | | 2x+2=3x-2/7 |

Equations solver categories